KETERAMPILAN MEMPREDIKSI DAN MENGKOMUNIKASIKAN PADA MATERI KELARUTAN DAN Ksp MENGGUNAKAN INKUIRI TERBIMBING - Andri Kasrani; Ila Rosilawati; Nina Kadaritna (Universitas Lampung, 2014)
This research aimed to describe the skill of prediction and communication on the solubility and Ksp matter by using guided inquiry learning models for high, intermediate and low groups of student. The subjects werestudents of class XI IPA3SMA YP Unila Bandar Lampung. This research used the pre-experimental method, a one-shot case study design, and descriptiveresearch statistics. The results showed that the skill of prediction in high levelgroup 70% were excellent, 30% were good; in intermediate level group, 30%were excellent, 60% were good, and 10% were enough; in the low level group,10% were excellent, 40% were good, 40% were enough, and 10% were less. Theskill of communication in high level group 40% were excellent, 50% were good, and 10% were enough; in intermediate level group, 10% were excellent, 65% were good, and 25% were enough; in the low level group, 10% were good, 40% were enough and 50% were less.Keywords: guided inquiry, skill of prediction and communication, solubility andKsp.